HUBUNGAN KESUKSESAN KARIER SUBYEKTIF DAN KECEMASAN PADA PEREMPUAN BEKERJA DI JABODETABEK - Gabrielle Deanella; Puji Tania Ronauli (MANASA, 2020)
The aim of this research is to identify the relationship between subjective career success andwork anxiety which often felt by working women. This study is a quantitative research with acorrelational explanatory design. Participants for this research is consisted of 129 women aged19 to 65 years who work in the Jabodetabek area. Data were collected using two measurementtools namely, the Subjective Career Success Inventory (SCSI) (24 items, α = 0.955) and theHamilton Anxiety Rating Scale (HAM-A) (14 items, α = 0.906). Through the Spearman (1-tailed) calculation, the result of this hypothesis test showed a correlation coefficient of ???????? =−.224 and a significance level of ???? = .005 (???? > 0.05). These two variables are negativelyrelated to each other. The result shows that the more working women feel her career successsubjectively positive, the less anxiety she has to her work and vice versa. It is recommendedfor companies to pay attention and to overcome the level of women employee anxieties bysocializing the importance of a subjective career success and arranging interventions withsimilar themes. The researcher added that the level of anxiety experienced by the participantsmight also be caused by changes in working situation during Covid-19.